Memórias Póstumas de Brás Cubas: atualização e virtualidade na construção da literatura como memorial - Onodera, Daniele dos Santos Souza (2011)
The objective of this paper is to discuss how the literary form competes in the building of a historical and social memory of the temporality in the novel Memórias Póstumas de Brás Cubas by Machado de Assis considering the period in which it was produced. Firstly, it was used Lukács'studies (2000) to talk about the fact that the novel did not have a formal pre adaptation and because of that permitted, more than in other genres, the transposition from reality to the literary plan. Secondly, Machado de Assis was situated in relation to social and political aspects that surrounded the daily life in the Brazilian empire, and also in relation to literary practice and literary plan. Finally, this paper focused on the analysis of the memorial report by the dead-author Brás Cubas. Using the famous metaphors created by Pierre Lévy (1996) virtualization and "update". it was verified how the update about his life imerse in the memorial universe (virtual) made the dead-author to reveal the social and historical context of the court in the 19th century simultaneously.